Researcher recommendation to fact checkers leveraging on knowledge graphs and topic-based ranking - Keya, Farhana; Svátek, Vojtěch, 1967 prosinec 1.-; Kordík, Pavel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Fact-checking is an activity that aims to solve the global issue of misinformation spread. As automated fact-checking approaches have been recently popular, they need pre-existing ground-truth evidence, which is scarce and dispersed in scientific circumstances. To help the fact-checker with COVID-19-related scientific misinformation detection, we aim to enhance a knowledge graph where the researcher’s contact information will be stored with their research expertise area so that when fact-checkers will verify any COVID-19-related scientific misinformation. There is extensive communication of researchers for a particular research domain. Fact-checkers can be dilemma as to which researcher they should contact first. To solve this issue, we are also developing an algorithm to rank researchers’ profiles, utilizing their experience and research interests. We aim to develop a system that suggests domain experts using enhanced knowledge graph.
Vedoucí práce: Vojtěch Svátek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses